2019
DOI: 10.1186/s13000-019-0903-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of p-Stat3 Y705 immunohistochemistry in glioblastoma prognosis

Abstract: BackgroundIn spite of the multimodal treatment used today, glioblastoma is still the most aggressive and lethal cerebral tumour. To increase survival in these patients, novel therapeutic targets must be discovered. Signal transducer and activator of transcription 3 (Stat3), a transcription factor that controls normal cell differentiation and survival is also involved in neoplastic celltransformation. In this study we evaluated the immunohistochemical expression of pY705-Stat3 in patients with primary glioblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In addition, the research group reported an association between the ectopic expression of miR-155 and the growth of HCC cells, while its downregulation inhibited their growth [ 182 ]. The oncogenic behavior of hepatic miR-155 was also confirmed by Yan et al They correlated its elevation with the downregulation of SOCS1, which activated STAT3, previously confirmed as an important prognostic biomarker in other cancers, such as glioblastoma [ 183 ], and further downregulated MMP9 expression, consequently promoting HCC tumor invasiveness [ 184 ]. Research on animal models shows that hepatic miR-155 overexpression has a protective role in NAFLD and, paradoxically, a tumor-promoting one in HCC [ 185 ].…”
Section: Dysregulated Mirnas and Their Role In Nafld-related Hccmentioning
confidence: 83%
“…In addition, the research group reported an association between the ectopic expression of miR-155 and the growth of HCC cells, while its downregulation inhibited their growth [ 182 ]. The oncogenic behavior of hepatic miR-155 was also confirmed by Yan et al They correlated its elevation with the downregulation of SOCS1, which activated STAT3, previously confirmed as an important prognostic biomarker in other cancers, such as glioblastoma [ 183 ], and further downregulated MMP9 expression, consequently promoting HCC tumor invasiveness [ 184 ]. Research on animal models shows that hepatic miR-155 overexpression has a protective role in NAFLD and, paradoxically, a tumor-promoting one in HCC [ 185 ].…”
Section: Dysregulated Mirnas and Their Role In Nafld-related Hccmentioning
confidence: 83%
“…The role of STAT3 in tumor formation and progression has been extensively studied in many human cancers ( Kusaba et al, 2005 ; Diaz et al, 2006 ; Banerjee et al, 2016 ; Li et al, 2019 ; Susman et al, 2019 ; Marginean et al, 2021 ), including HNSCC ( Mali, 2015 ; Geiger et al, 2016 ). Aberrant activation of STAT3 leads to the increased expression of downstream target genes, leading to increased cell proliferation, cell survival, angiogenesis, and immune system evasion ( Yu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that STAT3/p-STAT3 is highly expressed in a variety of tumors and its activation product, p-STAT3, is associated with tumor grade and patient prognosis ( 33 , 34 ). As a major mediator of the JAK/STAT pathway, STAT3 may be an important regulator of tumor progression by enhancing aggressiveness or promoting EMT ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%